F0F1-ATPase Contributes to the Fluoride Tolerance and Cariogenicity of Streptococcus mutans - Li, Cheng; Qi, Cai; Yang, Sirui; Li, Zhengyi; Ren, Biao; Li, Jiyao; Zhou, Xuedong; Cai, Huawei; Xu, Xin; Peng, Xian (Frontiers in Microbiology, 2022)
The phenotypic traits of Streptococcus mutans, such as fluoride tolerance, are usually associated with genotypic alterations. The aim of this study was to identify adaptive mutations of S. mutans to gradient fluoride concentrations and possible relationships between the mutations and fluoride tolerance. We identified a highly resistant S. mutans strain (FR1000) with a novel single nucleotide polymorphism (SNP, -36G→T) in the promoter region of F0F1-ATPase gene cluster (SMU_1527-SMU_1534) resistant to 1000 ppm fluoride using the whole-genome Illumina PE250 sequencing. Thus, a -36G→T F0F1-ATPase promoter mutation from the parental strain S. mutans UA159 was constructed and named UA159-T. qRT-PCR showed that the F0F1-ATPase gene expression of both FR1000 and UA159-T was up-regulated, and fluoride tolerance of UA159-T was significantly improved. Complementation of Dicyclohexylcarbodiimide (DCCD), a specific inhibitor of F0F1-ATPase, increased fluoride susceptibility of FR1000 and UA159-T. Intracellular fluoride concentrations of fluoride tolerance strains were higher compared to UA159 strain as demonstrated by 18F analysis. Further validation with rat caries models showed that UA159-T caused more severe caries lesions under fluoride exposure compared with its parental UA159 strain. Overall, the identified -36G→T mutation in the promoter region of F0F1-ATPase gene drastically contributed to the fluoride tolerance and enhanced cariogenicity of S. mutans. These findings provided new insights into the mechanism of microbial fluoride tolerance, and suggested F0F1-ATPase as a potential target for suppressing fluoride resistant strains.